Prediction of pollutant concentration and ventilation control in urban bifurcate tunnel, China. (December 2018) - Li, Qiong; Chen, Chao; Yuan, Haoting; Wang, Luyao; Xu, Shuhui; Li, Yaru
Graphical abstract: Highlights: Pollutant mass transfer model in urban bifurcation tunnel was developed. Confluence and distributary ramps are significant to the pollutant concentration. Ramps reduce required air volume for tunnel ventilation. Abstract: The changes in the complex structural features and traffic characteristics of urban bifurcate tunnel have led to variation in the emission of pollutants and distribution of their concentration, and this presents new challenges to the operation of ventilation systems. A one-dimensional steady-state pollutant mass transfer model was developed to quantify the influence of the confluence and distributary ramps and determine the ventilation control. This model was based on the mass conservation theory, a scale model experiment and measurements, and was effectively verified by four-years field-measured data from three urban tunnels in Shanghai and Changsha, China. According to the calculation results of the model, the distribution of the CO pollutant concentration and the ventilation system control of the main tunnel in an urban bifurcate tunnel can be quantitatively evaluated under the corresponding traffic flow conditions. The results show that the combined effect of the confluence ramp on the increase pollutant concentration in the downstream segment of the main tunnel is limited, However, the distributary ramp has a significant effect on the decrease of pollutant concentration downstream in the main tunnel.